Wound Healing After Thermal Injury Is Improved by Fat and Adipose-Derived Stem Cell Isografts. Issue 1 (January 2015) - Loder, Shawn; Peterson, Jonathan R.; Agarwal, Shailesh; Eboda, Oluwatobi; Brownley, Cameron; DeLaRosa, Sara; Ranganathan, Kavitha; Cederna, Paul; Wang, Stewart C.; Levi, Benjamin
<x xml:space="preserve">Abstract</x> Patients with severe burns suffer functional, structural, and esthetic complications. It is important to explore reconstructive options given that no ideal treatment exists. Transfer of adipose and adipose-derived stem cells (ASCs) has been shown to improve healing in various models. The authors hypothesize that use of fat isografts and/or ASCs will improve healing in a mouse model of burn injury. Twenty 6 to 8 week old C57BL/6 male mice received a 30% surface area partial-thickness scald burn. Adipose tissue and ASCs from inguinal fat pads were harvested from a second group of C57BL/6 mice. Burned mice received 500 μl subcutaneous injection at burn site of 1) processed adipose, 2) ASCs, 3) mixed adipose (adipose and ASCs), or 4) sham (saline) injection (n = 5/group) on the first day postinjury. Mice were followed by serial photography until being killed at days 5 and 14. Wounds were assessed for burn depth and healing by hematoxylin and eosin (H&E) and immunohistochemistry. All treated groups showed improved healing over controls defined by decreased wound depth, area, and apoptotic activity. After 5 days, mice receiving ASCs or mixed adipose displayed a non-significant improvement in vascularization. No significant changes in proliferation were noted at 5 days. Adipose isografts improve some early markers of healing postburn injury. The authors demonstrate that addition of these grafts improves specific structural markers of healing. This improvement may be because of an increase in early wound vascularity postgraft. Further studies are needed to optimize use of fat or ASC grafts in acute and reconstructive surgery.